Implementasi Work-Life Balance dan Pengaruhnya terhadap Produktivitas Karyawan Bank BPR di Bukittinggi - Eka Febrianti; Andria Ningsih; Asnah Asnah (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2026)
This study aims to analyze the implementation of work-life balance and its impact on employee productivity at Bank BPR Bukittinggi. The research method used is a quantitative approach with data collection techniques through the distribution of questionnaires to 125 respondents who are active employees. Data analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with the help of the SmartPLS application version 4.0. The results of the study indicate that the implementation of work-life balance has a positive and significant impact on employee productivity. This indicates that the better the balance between work life and personal life is perceived by employees, the higher the resulting level of productivity. In addition, work-life balance dimensions such as flexible working hours, organizational support, and workload management have been shown to contribute significantly to improving employee performance. This study provides practical implications for the management of Bank BPR Bukittinggi to pay more attention to policies that support employee work-life balance in order to improve overall organizational productivity and performance.